Gastric metastases from primary breast cancers: rare causes of common gastrointestinal disorders. Issue 7 (6th July 2020) - Yuen, Tiffany; Liu, Eddie; Kohansal, Ali
Abstract : We report two cases of gastric metastases from primary breast cancers. In case 1, a 31-year-old woman with right-sided ductal breast carcinoma presented with nausea, vomiting and frank haematemesis, 8 months after mastectomy and adjuvant chemotherapy. An esophagogastroduodenoscopy (EGD) revealed multiple ulcerated gastric lesions secondary to metastatic adenocarcinoma from primary breast tumour. In case 2, an 84-year-old woman with a history of left lobular carcinoma presented with early satiety, 17 years after initial mastectomy and adjuvant endocrine therapy. An EGD revealed unspecific gastric mucosa with thickened and erythematous folds and biopsies revealed adenocarcinoma from primary breast carcinoma. Our cases demonstrate how gastric metastases have variable, non-specific clinical and endoscopic presentations. Symptoms may include nausea, vomiting, early satiety and gastrointestinal (GI) bleeding. Endoscopic appearance may range from thickened gastric folds to ulcerating lesions. Our cases demonstrate that gastric metastases should be considered in patients with breast cancer history presenting with GI symptoms.